Body dysmorphic disorder: Diagnosis, clinical aspects and treatment strategies - Rajiv Ahluwalia; Navneet Kaur Bhatia; Priyanka Sethi Kumar; Parvinder Kaur (Wolters Kluwer Medknow Publications, 2017)
Aim: With the increased demand to undertake dental aesthetic and reconstructive procedures, it is imperative for all dental clinicians to have an understanding of body dysmorphic disorder (BDD). Patient's preoccupations with perceived defect in appearance or excessive concern about minimal flaws are among diagnostic criteria of BDD. Such patients are difficult to please and often undergo cosmetic procedures such as orthodontic treatment. Methodology: Literature search in PubMed/MEDLINE was conducted from 1891 to 2015. A manual search of relevant articles and review was done and relevant data was collected and analysed. Results: One of the most common areas of preoccupation is the dento-facial region, with up to 20% of patients diagnosed with BDD expressing specific concern regarding their dental appearance. Conclusion: BDD patients often request multiple aesthetic procedures, but remain unsatisfied with their treatment results.